2018
DOI: 10.31466/kfbd.473808
|View full text |Cite
|
Sign up to set email alerts
|

ZnO:Eu Filmlerinin Mikroyapısal ve Optik Özellikleri

Abstract: Evropiyum (Eu) katkılı çinko oksit (ZnO) filmleri, ucuz ve basit bir metot olan sol jel metodu ile elde edilen çözeltiler kullanılarak p-tipi silisyum (p-Si) alttaşlar üzerine spin kaplama tekniği ile büyütülmüştür. Elde edilen ZnO filminin yapısal, morfolojik ve optik özellikleri üzerine Eu katkısının etkisi, sırasıyla X-ışını kırınım cihazı, taramalı elektron mikroskobu ve uv-vis spektrofotometresi kullanılarak araştırılmıştır. Filmlerin XRD spektrumlarından, bütün filmlerin hekzagonal wurtzite zinkit (ZnO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…In other words, ZnO, which is characterized by the hexagonal wurtzite structure, may exhibit different characteristics due to defects such as zinc interstitials and oxygen vacancies, which depend on the growth technique and growth parameters. Similar results were found also by many other authors [40,41]. Therefore, it can be suggested that the evaluation of ZnO's characteristics should be made taking the growth technique into consideration.…”
Section: Resultssupporting
confidence: 88%
“…In other words, ZnO, which is characterized by the hexagonal wurtzite structure, may exhibit different characteristics due to defects such as zinc interstitials and oxygen vacancies, which depend on the growth technique and growth parameters. Similar results were found also by many other authors [40,41]. Therefore, it can be suggested that the evaluation of ZnO's characteristics should be made taking the growth technique into consideration.…”
Section: Resultssupporting
confidence: 88%